Distant proximities : dynamics beyond globalization - Rosenau, James N. (Princeton, N.J. : Princeton University Press, 2003)
This book presents a work of vision that addresses the dizzying anxieties of the post-Cold War, post-September 11 world. It analyses just how complex these profound global changes have become.
Includes bibliographical references and index.
oif 30/10/15
Loan
Keywords: International relations